Transformation of Bandung City Tourism Marketing Strategy: Integrating Digital Technology and Local Wisdom for Global Competitiveness - Nidya Novalia; Tria Meisya Aziti (Global Research Collaboration, 2026)
Tourism destinations increasingly compete through digital visibility, distinctive identity, and strategic marketing capability. Bandung City has strong tourism potential through its creative economy, culinary attractions, urban heritage, and Sundanese cultural identity; however, these resources need to be strategically translated into effective marketing practices to support destination competitiveness. This study examines the relationships among digital technology integration, local wisdom, tourism marketing strategy, and global competitiveness, as well as the mediating role of tourism marketing strategy in these relationships. A quantitative explanatory approach was employed. Data were collected through questionnaires distributed to tourism-related stakeholders in Bandung City, including tourists, tourism business actors, destination managers, community members, and government-related tourism personnel. A total of 212 valid responses were analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that digital technology integration and local wisdom are positively associated with tourism marketing strategy. Both digital technology integration and local wisdom also show positive direct relationships with global competitiveness. Tourism marketing strategy demonstrates the strongest relationship with global competitiveness and partially mediates the relationships between digital technology integration, local wisdom, and global competitiveness. The model accounts for 58.3% of the variance observed in tourism marketing strategy, while the explained variance for global competitiveness is 64.7%. The results indicate that Bandung City’s tourism competitiveness depends not merely on the availability of digital tools or cultural resources, but on how effectively these assets are integrated into coordinated marketing initiatives. Because the data are cross-sectional and based on respondents’ perceptions, the identified relationships should be understood as associations rather than definitive causal effects.